Development of augmented reality (AR) SI MOPEM to improve teachers' understanding of learning models - Nurma'ardi, Hilda Dhaniartika; Oktaviani, Anna Maria; Antoni, Ahmad; Limas, Nida Nabilah (Indonesian Journal of Educational Development (IJED), 2025)
Based on the analysis, many teachers experience limitations in understanding the syntax of learning models that impact the quality of teaching and student competency. Therefore, the development of AR media becomes an effective solution. This study aims to develop AR-based SI MOPEM (Learning Model Syntax) media. This R&D research was conducted using a 4D development model. The population of this study was all elementary school teachers in Serang Regency, whose samples were taken using purposive sampling of 50 people in the same cluster. Data collection techniques included observation, interviews, documentation, questionnaires, and tests, while the instruments were validity sheets, teacher understanding tests, and self-assessment questionnaires. Overall, the validity test was in the very feasible category, and a limited trial with 12 teachers found SI MOPEM very practical (91.46%). The results showed that the effectiveness test resulted in a significant increase in understanding (paired sample t-test, p = 0.000) with an n-gain score of 0.63 (moderate category). Therefore, it is concluded that SI MOPEM is highly feasible, practical, and effective as a tool for understanding learning models interactively and independently. This research recommends conducting larger-scale testing and further developing SI MOPEM, such as adding features or integrating it with other platforms.